The impact of haemodilution and bypass pump flow on cerebral oxygen desaturation during cardiopulmonary bypass - A comparison of two systems of cardiopulmonary bypass. (July 2015) - Bennett, MJ; Weatherall, M; Webb, G; Dudnikov, SF; Lloyd, CT
Objective: To determine the influence of haemodilution, bypass flow rates and calculated oxygen delivery during cardiopulmonary bypass (CPB) with either a conventional CPB (C-CPB) circuit or a miniaturised (Mini-CPB) circuit on cerebral oxygen desaturation. The effect of minimal haemodilution with a Mini-CPB was investigated. Participants: Eighty patients scheduled for elective cardiac surgery. Intervention: Oxygenated haemoglobin (O2 Hb) and tissue oxygenation index (TOI) were measured with near-infrared spectroscopy (NIRS). Results: The average indexed bypass pump flow was significantly lower with Mini-CPB. When combined with haemoglobin concentration, the average oxygen delivery was the same between groups. Patients in the C-CPB group had a greater duration and severity of cerebral desaturation to a level <20% below baseline values, but none reached the depth and duration of the cerebral desaturation associated with poor outcome. Cerebral oxygen desaturation with C-CPB was significantly associated with low flows during bypass, whereas desaturation with Mini-CPB was associated with low perioperative haemoglobin concentration.